Some factors influencing the effective use of disinfectants and cleaning agents - W.P. Kortenbout (AOSIS, 1982)
Disinfection means the freeing of an article from some or all of its burden of live pathogenic microorganisms which might cause infection during its use. The term is a relative one and disinfection may be described as being partially or highly effective according to the proportion of pathogenic organisms killed or removed.